A FRAMEWORK FOR RELIGIOUS EDUCATION - McKay, Alexander (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1988)
The author constructs a general framework for religious education based on two hypotheses. The first is related to notions of the appropriate objectives for religious education in the public school setting, and second, these objectives have been linked to several theories of human development so that a trajectory or general framework emerges. As such, the conclusions drawn are based on theory rather than practise or classroom experience. The purpose is not to provide a methodological guide for the teaching of religious education, but rather to isolate and expand upon conceptions of the appropriate theoretical bases for the objectives and structure of religious education. RÉSUMÉ L’auteur élabore un schème général d’enseignement religieux qui s’appuie sur deux hypothèses. La première est liée aux notions d’objectifs adaptés à l’enseignement religieux à l’école publique et selon la seconde, ces objectifs seraient liés à plusieurs théories du développement humain de telle sorte qu’on pourrait en tirer une démarche ou un schème géneral. C’est pourquoi, les conclusions tirées s’appuient sur la théorie plutôt que sur la pratique ou l’enseignement en place. L’objectif n’est pas de fournir un guide méthodologique de l’enseignement religieux, mais plutôt d’isoler les concepts des fondements théoriques des objectifs et de la structure de l’enseignement religieux et d’extrapoler à partir de ceux-ci.